Pengaruh Motivasi Terhadap Minat Mahasiswa Akuntansi untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) - Meli Ana; Jaeni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to examine how much influence on students to follow the accounting profession education. The population of this study were students majoring in accounting from state universities and private universities in the city of Semarang. The sample of this study amounted to 100 respondents from university students UNES, UNDIP, UNISBANK, USM, UNIMUS, STIE BPD JATENG, UDINUS, UPGRIS. The independent variables in this study are quality motivation, career motivation, economic motivation, and social motivation. While the dependent variable is student interest in participating in PPAk. The data was collected by using a questionnaire, and the data was analyzed using the multiple linear regression method. The results show that quality motivation of 0.320 has an effect on student interest in PPAk, career motivation of -0.118 has no effect on student interest in PPAk, economic motivation of -0.096 has no effect on asking students to take PPAk, social motivation of -0.141 has no effect on asking students to take part PPAk. The conclusion shows that motivation has no effect on student interest in taking the Accounting Profession Education (PPAk) by 3.098%. Based on these findings, it is suggested to the PPAk organizing body to always develop the PPAk curriculum. Keywords: Motivation career, motivation economic, motivation social, motivation quality, on student interest in participating in PPAk.